Evaluasi Manfaat Penerapan Program Kesehatan Gratis di Kabupaten Belu Tahun 2021-2024 - Januario Mulle; Melkisedek Noh Bernabas Cervesius Neolaka; Ardy Yosafat Pandie; Delila Angelina Nahak Seran (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2026)
This study aims to evaluate the implementation of the Free Health Program in Belu Regency during 2021–2024 using William N. Dunn’s public policy evaluation framework, focusing on effectiveness, adequacy, equity, and responsiveness. A qualitative method with a phenomenological approach was employed to explore the experiences and perceptions of stakeholders, including the Health Office, BPJS Health, health workers, and community beneficiaries. Data were collected through interviews, observations, and document analysis, and analyzed using descriptive qualitative techniques with triangulation to ensure validity. The findings indicate that the program has been effective in improving access to healthcare services and reducing financial burdens, as reflected in increased JKN participation and the achievement of Universal Health Coverage (UHC). In terms of adequacy, the program is supported by sufficient budget allocation, infrastructure, and comprehensive health services, although challenges remain in the distribution of medical personnel and drug availability. From an equity perspective, the program has reached all regions administratively; however, functional disparities persist due to geographical conditions and uneven resource distribution. Meanwhile, the program demonstrates a relatively high level of responsiveness through complaint-handling mechanisms and alignment with local socio-economic conditions. Overall, the program has provided significant benefits, but improvements are needed in service quality, resource distribution, and long-term sustainability.